ELECTROACOUSTIC EXPERIMENTS IN FRENCH FILM MUSIC: ON THE ISSUE OF PREREQUISITES / ЭЛЕКТРОАКУСТИЧЕСКИЕ ЭКСПЕРИМЕНТЫ В КИНОМУЗЫКЕ ФРАНЦИИ: К ВОПРОСУ О ПРЕДПОСЫЛКАХ - Platonova Olesia A. / Платонова О.А. (Наука телевидения)
The article analyzes the phenomena of European art of the first half of the 20th century, which not only prepared the birth of electroacoustic music, but also contributed to the dialogue between this trend of academic art and film music. The new view on the phenomenon of sound was the result of scientific and technological progress, powerful social transformations, and a change in the worldview paradigm. The first part of the article discusses the idea of autonomous sound in the works of Luigi Russolo, the concept of “liberation of sound” in the music of Edgar Varèse, and the role of noise design in the creative actions of Dadaists and performances of Antonin Artaud’s “théâtre de la cruauté” (“theatre of cruelty”). The second part is devoted to an in-depth study of sound-noise experiments in the French film music of the 1930s and 1940s. Analyzing samples of musical and noise collages (collaborations of Jacques Tati and Jean Yatove in the film Jour de fête, René Clair and Georges Auric—in À nous la liberté, Jean Vigo and Maurice Jaubert — in L’Atalante, Jean Renoir and Joseph Kosma—in La Bête humaine); methods of manipulating the optical track and the “partition rétrograde” (the product of the “co-authorship” of directors Jean Grémillon and Julien Duvivier and composers Alexis Roland-Manuel and Maurice Jaubert); examples of enriching the timbre palette of film music through electronic instruments (ondes Martenot in the music of Arthur Honegger, Adolphe Borchard, Maurice Thiriet to the films of Abel Gance, Dimitri Kirsanoff, Sacha Guitry, Marcel L’Herbier) in the context of global trends in art and technology, the author comes to the conclusion that by the beginning of the 1950s, the ground for electroacoustic experiments and their immediate introduction into film music was fully prepared, and that in the previous years, filmmakers had realized the expressive power of noise and electronic sounds. Статья посвящена анализу тех явлений европейского искусства первой половины XX века, которые не просто подготовили рождение электроакустической музыки, но и способствовали диалогу между данным направлением академического искусства и киномузыкой. Новый взгляд на феномен звука стал результатом научно-технического прогресса, мощных социальных преобразований, смены мировоззренческой парадигмы. В первой части статьи рассматривается идея автономии шумов в творчестве Луиджи Руссоло, концепция «освобождения звука» в музыке Эдгара Вареза, роль звукошумового оформления в творческих акциях дадаистов и спектаклях «крюотического театра» («театра жестокости») Антонена Арто. Вторая часть посвящена углубленному изучению звукошумовых опытов во французской киномузыке 1930-х–1940-х годов. Анализируя образцы музыкально-шумовых коллажей (сотворчество Жака Тати и Жана Ятова в фильме «Праздничный день», Рене Клера и Жоржа Орика в картине «Свободу нам!», Жана Виго и Мориса Жобера — в «Аталанте», Жана Ренуара и Жозефа Косма — в «Человеке-звере»), способы манипуляций с оптической дорожкой и «метод ретроградной партитуры» (результат «соавторства» режиссеров Жана Гремийона, Жюльена Дювивье и композиторов Алексиса Ролан-Мануэля и Мориса Жобера), примеры обогащения тембровой палитры киномузыки за счет электронных инструментов (волны Мартено в музыке Артюра Онеггера, Адольфа Боршара, Мориса Тирье к картинам Абеля Ганса, Димитрия Кирсанова, Саши Гитри, Марселя Л’Эрбье) в контексте мировых тенденций в искусстве и технологиях, автор приходит к выводу, что к началу 1950-х годов почва для электроакустических экспериментов и их незамедлительного внедрения в киномузыку была полностью подготовлена, а кинематографисты за предыдущие годы уже сумели осознать выразительную силу шумов и электронных звучаний.